An exploration of menstruation hygiene management among high school learners: the case of Fezeka High School, Gugulethu - Chirambo, Tereza (Department of Social Development, 2021)
Menstruation is an issue of great importance. Today, despite menstruation being a natural process, it affects the education of girls. A qualitative study was conducted in Gugulethu, where face to face interviews were conducted with nineteen girls from Fezeka High school. The purpose of the study was to explore menstruation hygiene management among high school learners. Specifically, the study explored the experience of menstruation hygiene, the challenges faced during menstruation, coping mechanisms during menstruation and the support system available for menstruating girls. The study adopted a qualitative design because such an approach helps in examining a phenomenon from the subject's perspective. The findings established that girls knew about menstruation before the first onset. A mother or grandmother was a commonly mentioned source of information on menstruation. The study further showed that most girls use sanitary materials supplied by a mother or guardian, during menstruation. It showed that challenges that girls experienced include: emotional changes; physical discomfort (stomach cramps, tiredness, and loss of appetite); public shame; changes in social interactions and inadequate sanitation hygiene facilities. Additionally, the study showed that most girls still attend school during menstruation. The girls coped by wearing many clothes to prevent leaks; constantly checking their skirts; sitting differently on the chairs and taking medication to relieve menstrual pain. Friends were also found to help in alleviating the challenges faced by the girls; they were the main social support system for girls during menstruation. However, while school attendance was maintained, class participation was shown to be affected because of discomfort and menstrual pains. Based on the research findings, the study concluded that there is inadequate sanitation and hygiene for girls to comfortably change sanitary materials and there is a lack of communication on menstrual hygiene management between the girls and their teachers. As such, integrating menstruation hygiene management in the curriculum and providing for appropriate facilities to ensure privacy is recommended.